Forces Widening Occupational Wage Differentials - Perlman, Richard (The Review of Economics and Statistics, 1958)
A CCORDING to generally accepted wage 11 theory, the forces affecting the occupational wage structure in the past operated to narrow skill differentials. Statistical evidence supported this theory. This paper presents the view that though the skill differential has narrowed in the past, the current tendency is for a stabilized differential, and the future trend is toward a widening differential. Before analyzing the forces affecting the differential, existing statistical studies of skilledunskilled wage relationships are reviewed briefly in order to describe recent trends in differentials. Throughout the study only both extremes of the occupational wage scale -the skilled and unskilled wageare discussed; a more comprehensive study of changes in the occupational wage structure would entail discussion of movements of all classes within the range, in particular, fluctuations in semi-skilled wages. What follows pertains to the American scene, but in developing the theoretical arguments references will be made to foreign experience.